O bibliotecário: formação, perfil e atuação profissional - PASSINHO, Liniker Feio (2017)
Analysis of the formation, profile and performance of the librarian, with the general objective of analyzing the activity of the librarian in legal information units. The research carried out has a basic nature, with a qualitative approach to the problem. From the point of view of its objectives, an explanatory research is presented, the bibliographical research being a technical procedure. Carried out in three stages: the research addresses the concept and the various aspects that constitute the professionals of the information; Search in loco of this professional in order to determine if the professional curriculum requested by the employers and the activity developed by the librarian is in accordance with the attributions given to them; And empirical research carried out by means of observation, the study area being the Library of the Antônio Koury Judge of the Court of Justice of the State of Pará. The results allow to verify as skills and abilities necessary to the librarian before the dynamic panorama of information and communication technologies: Be aware of sources of information independent of their support and have proficiency in the use of information sources are legal or not. In conclusion, one can see the importance of continuous information for the professional, since the training models and the syllabuses of undergraduate courses can hardly keep up with the speed of events and technological advances.